Revitalization of Aqidah Learning: A Managerial Analysis of Aqidah Teaching Material Development at Islamic State Higher Education Institutions (PTKIN) - Asyadily, Muhamad Hasan; Mufid, Fathul (QUALITY, 2025)
This study examines the revitalization of Aqidah learning by analyzing the management of teaching material development within the Aqidah course cluster at State Islamic Higher Education Institutions (PTKIN). The Aqidah course cluster often receives limited attention and is considered one of the least developed disciplines in Islamic studies. The field is generally perceived as unappealing due to its focus on historical conflicts. Furthermore, the historical-textual approach often results in interpretations centered on conflict, potentially fostering sectarian fanaticism. This qualitative study utilized primary data collected from five PTKINs in Indonesia through analytical-descriptive methods. Data were collected through interviews and documentation, both of which were analyzed using triangulation techniques. Findings indicate that the Aqidah course cluster significantly contributes to the Aqidah and Islamic Philosophy curricula. UIN Syarif Hidayatullah Jakarta allocates 20% of its total course offerings to the cluster, followed by UIN Walisongo Semarang (19.40%), UIN Sultan Maulana Hasanuddin Banten (18.42%), UIN Sunan Kudus (18.46%), and UIN Sunan Kalijaga Yogyakarta (12.73%). Managerial analysis of Aqidah teaching material development encompasses theoretical and conceptual aspects, incorporating local Indonesian theological insights, multidisciplinary integration, engagement with classical texts, and applied theology. These developments aim to enhance the relevance of Islamic theology by incorporating faith-based values into contemporary life. This study provides a managerial framework and empirical evidence that can serve as a foundation for revitalizing the Aqidah curriculum in PTKIN and introduces a contextual theological framework.